The effectiveness of household waste management based on the waste alms concept by elementary school students - Aliet Noorhayati Sutisno; Noor Novianawati; Dewiantika Azizah (International Journal of Education and Humanities, 2021)
This study aims to find out effectiveness of household waste management based on the concept of waste alms carried out by students and parents of elementary school students in collaboration with the school. This study is quantitative descriptive research that was conducted on 100 students in one of Cirebon sub-district elementary schools. In this research, students donate domestic waste every week. The Purpose of this study was to provide students with an understanding of the importance of protecting the environment trough reducing household waste. The observation sheet was used as the research instrument of this study. The results showed that the concept of waste alms in household waste management which is integrated with elementary school education units can reduce 2.17% of the volume of waste growth